2011
DOI: 10.4049/jimmunol.1003597
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-1–Processed Cytokines IL-1β and IL-18 Promote IL-17 Production by γδ and CD4 T Cells That Mediate Autoimmunity

Abstract: IL-1β plays a critical role in promoting IL-17 production by γδ and CD4 T cells. However, IL-1–targeted drugs, although effective against autoinflammatory diseases, are less effective against autoimmune diseases. Conversely, gain-of-function mutations in the NLRP3 inflammasome complex are associated with enhanced IL-1β and IL-18 production and Th17 responses. In this study, we examined the role of caspase-1–processed cytokines in IL-17 production and in induction of experimental autoimmune encephalomyelitis (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
263
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(284 citation statements)
references
References 34 publications
18
263
0
3
Order By: Relevance
“…Therefore, we next investigated whether cytokines known to induce IL-17 production in mature γδ T-cells also participate in the programming of the γδ17 effector fate. Previous work suggested that γδ17 cells differ from their Th17 counterparts in terms of cytokine requirements, with IL-1β, IL-21, and IL-23 implicated as drivers of IL-17 production by γδ17 cells, whereas IL-6 is a key cytokine for Th17 cells 1719, 3235 . Therefore, we assessed whether adding combinations of IL-1β, IL-21, and IL-23 to the KN6/MEF co-cultures could result in the functional programming of the γδ17-effector subtype.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we next investigated whether cytokines known to induce IL-17 production in mature γδ T-cells also participate in the programming of the γδ17 effector fate. Previous work suggested that γδ17 cells differ from their Th17 counterparts in terms of cytokine requirements, with IL-1β, IL-21, and IL-23 implicated as drivers of IL-17 production by γδ17 cells, whereas IL-6 is a key cytokine for Th17 cells 1719, 3235 . Therefore, we assessed whether adding combinations of IL-1β, IL-21, and IL-23 to the KN6/MEF co-cultures could result in the functional programming of the γδ17-effector subtype.…”
Section: Resultsmentioning
confidence: 99%
“…IL-17 could not be detected in PBMCs or in purified gd T cells, even in the presence of IL-1b and IL-18, which have been implicated in the regulation of IL-17 production in humans and mice (46,53), respectively. The requirements for the differentiation of IL-17-producing human Vg9Vd2 T cells were defined recently (46).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, ROR γ t expression is up‐regulated by IL‐1 β and IL‐23 in a synergistic manner 20. The inflammatory cytokine IL‐18,53 complement C5a,54 the ligand of Toll‐like receptors 1 and 2, and dectin‐155 also induce IL‐17 in collaboration with IL‐23. Although γδ 17 cells typically behave as innate‐like immune cells, IL‐17 induction by TCR signalling is also reported.…”
Section: The Mechanism Of Il‐17 Production In γδ17 Cellsmentioning
confidence: 99%